Evaluation of the use of chemical pads to mimic latent fingermarks for research purposes. (September 2020) - Steiner, Romain; Moret, Sebastien; Roux, Claude
Highlights: Artificial fingermarks produced from three commercial chemical pads using rubber stamps. Detection techniques applied and results compared with real fingermarks. Concentrations of target compounds are too high in chemical pads. Pad behaviour unpredictable and differences observed across detection techniques. Use of these chemical pads is not recommended. Abstract: Fingermark detection is in constant evolution, with new techniques being developed and existing ones being continuously optimised. Recently, researchers have begun to express interest in artificial fingermark secretions to overcome the issues arising from the variability of fingermark composition. Some of these artificial secretions have started to appear on the market in the form of pads that can be used to deposit fingermarks with a known and controlled composition. This study aimed at assessing the reliability of three commercially-available pads by comparing the results to those obtained by real fingermarks, using six detection techniques (1, 2-indanedione/zinc, ninhydrin, cyanoacrylate followed by rhodamine 6G staining, gold/zinc vacuum metal deposition, and physical developer) on five substrate types (copy and recycled paper, acetate, glass, and glossy paper). The results showed that the artificial fingermarks deposited with these pads reacted in an unreliable way, notably when treated with complex detection techniques such as Physical Developer. Further, the high concentration of some of the target compounds found in the artificial secretion led to an over performance of some detection techniques, which could mislead the operator to overestimating the efficiency of a given method. The resulting artificial fingermarks are considered too dissimilar to real fingermarks to be used as quality control standards and better simulants need to be found for a more efficient and realistic control of the variability.